A Comparative Study of Traditional and Quiz Team-Type Cooperative Learning Approaches on Students' Academic Performance in Geography - Rahman, Muhammad Fauzi (CV Bumi Spasial, 2024)
This Classroom Action Research conducted at Madrasah Aliyah Negeri Asahan, Asahan Regency, in the academic year 2018/2019, investigates the efficacy of the Quiz Team Type Cooperative Learning Model (QTCLM) on enhancing student engagement and academic performance in Anthroposphere studies within class XI-IPS2. Specifically, it aims to assess: (1) the variation in student learning activities, and (2) the improvement in student learning outcomes following the QTCLM implementation. The research, adopting a Class Action Research (CAR) methodology, involved the entirety of the XI-IPS2 class, comprising 28 students. Data were amassed utilizing indirect communication techniques and systematic observation, subsequently analyzed through descriptive quantitative methods. Findings reveal a notable escalation in student learning activities from an initial 56.84% in Cycle I to 69.99% in Cycle II post-QTCLM application. Concurrently, student learning outcomes exhibited a significant rise from 71% in Cycle I to 87% in Cycle II. This improvement indicates that the objectives of classical completion have been satisfactorily achieved. The results corroborate the action hypothesis posited at the outset of the study: Implementing the QTCLM in teaching Anthroposphere material in class XI-IPS2 at MAN Asahan effectively enhances student participation and academic achievement, ensuring a minimum of 85% classical completeness. This research underscores the potential of interactive and cooperative learning strategies in fostering a more engaging and fruitful educational environment.